Mechanisms of Antibacterial Action of Quinoxaline 1,4-di-N-oxides against Clostridium perfringens and Brachyspira hyodysenteriae - Xu, Fanfan; Cheng, Guyue; Hao, Haihong; Wang, Yulian; Wang, Xu; Chen, Dongmei; Peng, Dapeng; Liu, Zhenli; Yuan, Zonghui; Dai, Menghong (Frontiers in Microbiology, 2016)
Quinoxaline 1,4-di-N-oxides (QdNOs) are a class of bioreductive compounds, however their antibacterial mechanisms are still unclarified. The aim of this study was to assess the ability of two representative QdNO drugs, cyadox (CYA) and olaquindox (OLA), to produce reactive oxide species (ROS) in Gram-positive anaerobe Clostridium perfringens CVCC1125 and Gram-negative anaerobe Brachyspira hyodysenteriae B204. In addition, the effects of QdNOs on the integrity of bacterial cell walls and membranes as well as the morphological alterations and DNA oxidative damage in C. perfringens and B. hyodysenteriae were analyzed. It was demonstrated that under anaerobic conditions, QdNOs were metabolized into the reduced products which did not show any antibacterial activity. A significant dose-related increase of intracellular ROS level and intracellular hydroxyl radicals were evident in bacteria exposed to QdNOs. The result of biochemical assay showed that the cell walls and membranes of the bacteria treated with QdNOs were damaged. After exposure to 1/2MIC to 4MIC of CYA and OLA, C. perfringens and B. hyodysenteriae became elongated and filamentous. Morphological observation with scanning and transmission electron microscopes revealed rupture, loss of cytoplasmic material and cell lysis in QdNO-treated bacteria, indicating serious damage of cells. There was an increase of 8-OHdG in the two strains treated by QdNOs, but it was lower in Gram-positive than in Gram-negative bacteria. Agarose gel electrophoresis showed the degradation of chromosomal DNA in both of the two anaerobes treated by QdNOs. The results suggest that QdNOs may kill C. perfringens and B. hyodysenteriae via the generation of ROS and hydroxyl radicals from the bacterial metabolism of QdNOs, which cause oxidative damage in bacteria under anaerobic conditions.